Dear Zoe Ukhona: a Journey through Infertility and Adoption - Mandela, Zindzi (Saga Egmont, 2023)
In English for the first time, with a foreword written by Zindzi Mandela, daughter of Nelson Mandela, this is a heartbreaking memoir of infertility, adoption, and fatherhood from one of Denmark’s most beloved tv personalities. One summer evening, on a blind date that is almost cancelled, Pelle Hvenegaard meets Caroline. He knows right away that this woman is the love of his life and the mother of his children. Their path to a family is not smooth. But after six years of infertility and the trials of the adoption system, they finally open the doors of their Copenhagen home to little Zoe Ukhona. Pelle’s account, told through letters to his daughter, is brutally honest, heart-wrenchingly tragic, and yet filled with warmth and good humour. It is a story of love, family, and hope. Highly recommended to those moved by Sarah Sentilles’ "Stranger Care" and "Finding Chika" by Mitch Albom. Pelle Hvenegaard first became world famous at twelve years old when he played the lead role in Bille August's Oscar-winning film "Pelle the Conqueror". A career in television and broadcast journalism followed. He has written four books on themes of adoption, love and identity.